ANALISIS PERTUMBUHAN GMELINA (Gmelina alborea.Roxb) DAN MAHONI (Swietenia magrophylla.King ) di GORONTALO - Sandalayuk, Daud (Universitas Gorontalo, 2018)
To know the growth analysis of Gmelina ( Gmelina alborea.Roxb ) and Mahoni (Swietenia magrophylla.King). It is necessary to look at the growth at a certain period in which a certain moment of growth will decrease so that the consideration in the maintenance can be done very evectively and consideration to harvest as needed in the processing of sawn timber or playwood. Mean Growth at age 10, diameter of gmelina 2,4 cm / tree / year, total volume 144,43 m3 / ha, MAI 14,44 m3 / atun, CAI 28,46 m3, Medium point of intersection of MAI and CAI occurred at age 15 years with total volume 251,80 m3 / ha. The growth of Mahogany at the age of 20 years after the measurement in the field with the width of I ha of 510 trees with an increase of diameter 1.38 cm / year, the number of Volume 174.35 m³ / ha and MAI 8.72 and CAI 12.58. At the time when MAI 9.37 and CAI 9.27 were at one point then it was allowed to harvest with age 30 years with a total voLume of 281.03 m3 / ha. This growth analysis can be used to analyze a tree type and help in analyzing an industrial plant where we want is a shorter age for harvesting so that time and cost are not much wasted